Family and ways to represent it - Ke, Queenie (Nanyang Technological University, 2020)
From the get-go, ​Family and ways to represent it started off as a project that wishes to heal estranged familial relationships. As the project progressed, the project shifted to one which looked at representation of family in our contemporary society. Family and ways to represent it aims to question the practice of photography as a family function and hopes to push the boundaries of the aforementioned.